Q: How do i solve y f 1 2x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Solve for y: f(-5)=13+2x

I assume you mean: f(x) = 2x - 1 There is really nothing to "solve" here. This is the description of a function. For a specific value of "x", you can replace that value, to find out the value of the function. This is basically the same as evaluating: y = 2x - 1

y = f(x) = (2x + 1)/(x - 1)y*(x - 1) = (2x + 1) xy - y = 2x + 1xy - 2x = y + 1x(y - 2) = y + 1so x = (y + 1)/(y - 2) assuming yâ‰?2.So the inverse function is f-1(x) = (x + 1)/(x - 2)

-530

X = 0 (zero) Y = -1 (neg 1)

Related questions

Solve for y: f(-5)=13+2x

I assume you mean: f(x) = 2x - 1 There is really nothing to "solve" here. This is the description of a function. For a specific value of "x", you can replace that value, to find out the value of the function. This is basically the same as evaluating: y = 2x - 1

get it to y= -2y = 1 - 2x y = x - 0.5

y = f(x) = (2x + 1)/(x - 1)y*(x - 1) = (2x + 1) xy - y = 2x + 1xy - 2x = y + 1x(y - 2) = y + 1so x = (y + 1)/(y - 2) assuming yâ‰?2.So the inverse function is f-1(x) = (x + 1)/(x - 2)

y = 2x -1 y = 5x -13 So: 5x -13 = 2x -1 5x -2x = 13 -1 3x = 12 x = 4 and by substituting y = 7

-530

y= -2x

X = 0 (zero) Y = -1 (neg 1)

If you have a function, such as y=2x also written as f(x)=2x, then you plug in the number. So for example if x=1 then you have y=2 or f(1)=2.

If: x+y = 4 and y = 2x+1 Then: 4-x = 2x+1 => 3 = 3x => 1 = x So by substitution: x = 1 and y = 3

To find the x-intercept, set y equal to zero (because that is where the line crosses the x-axis) and solve for x: y = 2x + 1 0 = 2x + 1 -2x = 1 x = -1/2 To find the y-intercept, set x equal to zero and solve for y: y = 2x + 1 y = 2*0 + 1 y = 1 The graph of this equation is a straight line that extends infinitely in both directions, therefore there is no "middle point."

I will assume your function is f(x) = 2x + 1 (answers.com eliminates some symbols from questions).First, you write this as:y = 2x + 1Next, you exchange "x" and "y":x = 2y + 1This is not strictly necessary, but the idea is that the final result is, once again, expressed in terms of "x".Finally, you solve this new equation for "y":y = ...You can then write this as a function if you wish; just replace "y =..." with "f(x) =...".